IMPROVING THE EFFECTIVENESS OF THE EDUCATIONAL PROCESS SYSTEMATIC APPROACH - Abdullayev Safibullo Khabibullayevich; Ulukhanov Ibrokhim Tokhtakhojaevich; Abdulnazarov Dilmurod the son of Azamjan; Qayumov Zairbek Zafarzhan (American Journals, 2023)
The article focuses on the issues of modernizing the educational system, restructuring it structurally, changing and updating educational programs, taking into account the modern achievements of Education, Science, Technology and technology, the economy and culture at the world level. In this regard, it is envisaged to widely master advanced technologies, integrate continuous education with science and production in the development of economic issues, entrepreneurship, small and private business, introduce a differentiated approach to education in accordance with the abilities and capabilities of students, create advanced pedagogical technologies of education, the basis for improving the organization and management of pedagogical processes.
Keywords: educational modernization, value, virtue, environment, pedagogical process, advanced technologies.